2021
DOI: 10.3390/nu13020558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synbiotic Supplementation on Chronic Inflammation and the Gut Microbiota in Obese Patients with Type 2 Diabetes Mellitus: A Randomized Controlled Study

Abstract: The aim of this study was to investigate the effects of 24-week synbiotic supplementation on chronic inflammation and the gut microbiota in obese patients with type 2 diabetes. We randomized 88 obese patients with type 2 diabetes to one of two groups for 24 weeks: control or synbiotic (Lacticaseibacillus paracasei strain Shirota (previously Lactobacillus casei strain Shirota) and Bifidobacterium breve strain Yakult, and galactooligosaccharides). The primary endpoint was the change in interleukin-6 from baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 44 publications
1
50
0
2
Order By: Relevance
“…In total, 11 studies were performed with supplemental fiber interventions in both IBD and T2DM populations. Studies investigating <10 g/day of fiber supplementation did not show significant changes in disease-specific outcomes in T2DM patients [ 73 , 79 , 81 ]. Additionally, these interventions only resulted in changes in the microbiome when combined with a probiotic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 11 studies were performed with supplemental fiber interventions in both IBD and T2DM populations. Studies investigating <10 g/day of fiber supplementation did not show significant changes in disease-specific outcomes in T2DM patients [ 73 , 79 , 81 ]. Additionally, these interventions only resulted in changes in the microbiome when combined with a probiotic.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, these interventions only resulted in changes in the microbiome when combined with a probiotic. Specifically, Kanazawa et al found significantly more Lactobacillus and Bifidobacterium in the synbiotic group (containing Lactobacillus parasei , Bifidobacterium breve , and 7.5 g/day of GOS) compared to placebo, as well as a significant increase in Akkermansia muciniphilia compared to baseline [ 81 ]. Horvath et al also explored the effects of a synbiotic ( Lactobacillus and Bifidobacterium spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEfSe analysis is performed to identify differences in flora and types of microorganisms between groups, which aids the development of biomarkers ( 17 ). The size of the different species is represented by the length of the histogram (i.e., LDA score) ( 28 ). The histogram revealed that HF dams (red) had more of the Romboutsia genus and Akkermansia genus than did the CC dams (green).…”
Section: Resultsmentioning
confidence: 99%
“…Lactis W58 and Lc. Lactis W19 + Omnilogic Plus : GOS P11, FOS P6, konjac glucomannan P13 (E425), calcium carbonate (E170), zinc citrate 3-hydrate, vitamin D3 (cholecalciferol) and vitamin B2 (riboflavin) (E101) and a matrix containing maltodextrin, natural elderflower flavouring and Gum Arabic (E414) 1.5 × 10 10 CFU total + 8 g/day Obese adults with T2D 6 months = = ↓ hip circumference, ↓ zonulin, ↑ QoL (physical functioning), = glucose metabolism [ 288 ] L. acidophilus, B. lactis, B. longum, B. bifidum + GOS 15 × 10 9 CFU + 5.5 g/day Overweight/obese humans that underwent weight loss program 3 months ↑richness, ↑ Bifidobacterium , ↑ Lactobacillus , ↓ Prevotella , ↓ Gardnerella = = [ 289 ] L. acidophilus, B. lactis, B. bifidum, B. longum + inulin 1.5 × 10 10 CFU each +6 g/day Overweight or obese people with prediabetes 6 months = Not reported =food intake [ 278 ] 2 Bifidobaterium +5 Lactobacillus strains + FOS + inulin 1 × 10 9 /g (total) + 9.6 g + 110.4 g Overweight/obese humans 3 months ↑ Lactobacillus , ↑ E. coli , ↑ Enterococcus = Not measured [ 290 ] L. casei , L. paracasei , B. breve + GOS 3 × 10 8 CFU each + 7.5 g daily Obese humans with T2D 24 weeks ↑ Bifidobacterium , ↑ Lactobacillus , ↑ B. adolescentis , ↑ B. pseudocatenulatum = ↑ acetic and butyric acids in faeces [ 291 ] This table summarises recent studies, examining the unique effect of microbiota modifications on body weight and gut microbiota composition in people with ove...…”
Section: Dietary Interventions That Act On Body Weight and That Shape...mentioning
confidence: 99%